2014
DOI: 10.1007/s11743-014-1659-1
|View full text |Cite
|
Sign up to set email alerts
|

Detergency of Vegetable Oils and Semi‐Solid Fats Using Microemulsion Mixtures of Anionic Extended Surfactants: The HLD Concept and Cold Water Applications

Abstract: In spite of the increasing interest in cold temperature detergency of vegetable oils and fats, very limited research has been published on this topic. Extended surfactants have recently been shown to produce very promising detergency with vegetable oils at ambient temperature. However, the excessive salinity requirement (4-14 %) for these surfactants has limited their use in practical applications. In this work, we investigated the mixture of a linear C 10 -18PO-2EO-NaSO 4 extended surfactant and a hydrophobic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 38 publications
1
44
0
Order By: Relevance
“…Palm kernel oil was purchased from Mountain Rose Herbs (Eugene, OR, USA). The reported melting points of coconut and palm kernel oils are 27.5 C (current study) and 28.6 C (Do et al, 2015), respectively. The anionic extended surfactant used in this study was a branched alcohol propoxylate sulfate sodium salt with 14-15 carbon atoms with eight groups of PO (C 14-15 -8PO-SO 4 Na) with 93.84% active, as received from Sasol North America, Inc. (Lake Charles, LA, USA).…”
Section: Experimental Procedures Materialsmentioning
confidence: 60%
See 2 more Smart Citations
“…Palm kernel oil was purchased from Mountain Rose Herbs (Eugene, OR, USA). The reported melting points of coconut and palm kernel oils are 27.5 C (current study) and 28.6 C (Do et al, 2015), respectively. The anionic extended surfactant used in this study was a branched alcohol propoxylate sulfate sodium salt with 14-15 carbon atoms with eight groups of PO (C 14-15 -8PO-SO 4 Na) with 93.84% active, as received from Sasol North America, Inc. (Lake Charles, LA, USA).…”
Section: Experimental Procedures Materialsmentioning
confidence: 60%
“…The effect of varying the surfactant system on the impact of alcohol addition was also taken into consideration. The surfactant systems of C 14‐15 ‐8PO‐SO 4 Na, C 10‐16 ‐7EO‐OH (better solid coconut oil removal than C 10‐16 ‐9EO‐OH according to this current study, data not shown), and C 10 ‐18PO‐2EO‐SO 4 Na + SDOSS at 0.24/0.76 M fraction with 0.5 w/v% NaCl (an optimized surfactant formulation in previous study (Do et al, )) were selected to evaluate the impact of alcohol addition on solid coconut oil detergency. Figure shows that adding intermediate‐chain alcohols (1‐heptanol or 1‐octanol or 1‐nonanol) achieved the most significant level of solid coconut oil removal improvement for all three surfactant systems, demonstrating the robust nature of these alcohols as detergency additives.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Tongcumpou studied the removal of triolein by using a surfactant mixture system composed of a nonionic surfactant and two anionic surfactants 16 . Do studied the removal of vegetable oil and semisolid fats using a surfactant mixture system composed of an anionic extended surfactant and a branched surfactant 17 . Thathakit studied the removal of palm oil soil using a mixture of an anionic extended surfactant and a nonionic surfactant 18 , and Endo studied triolein removal using mixtures of a nonionic surfactant and ampholytic surfactant 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it becomes easy to form a middle-phase microemulsion, which provides both a high solubilization and ultralow IFT, leading to various applications, especially detergency 15 18 . Tanthakit et al 19 investigated palm oil removal from fabrics using microemulsionbased formulations based upon a mixed surfactant system of C 14 21 reported that a mixture of a linear extended surfactant C 10 -PO 18 -EO 2 -SO 4 Na and a hydrophobic twin-tailed sodium dioctylsulfosuccinate surfactant showed synergism in a Winsor type III microemulsion formation, leading to a high detergency performance of vegetable oils and semi-solid fats at a low salinity and a low washing temperature. Attaphong et al 22 studied the relationship of microemulsion formation of an extended surfactant and canola oil detergency at a low surfactant concentration and low washing temperature, and found that a good detergency performance at a low washing temperature corresponded with a lower IFT.…”
Section: Introductionmentioning
confidence: 99%